Intraoperative inking is superior to suture marking for specimen orientation in breast cancer. Issue 4 (3rd September 2019) - Altman, Ariella M.; Nguyen, David D.; Johnson, Benjamin; Marmor, Schelomo; Klein, Molly E.; Tuttle, Todd M.; Hui, Jane Yuet Ching
Abstract: Margin status is an important indicator of residual disease after breast‐conserving surgery (BCS). Intraoperatively, surgeons orient specimens to aid assessment of margins and guide re‐excision of positive margins. We performed a retrospective review of BCS cases from 2013 to 2017 to compare the two specimen orientation methods: suture marking and intraoperative inking. Patients with ductal carcinoma in situ, T1/T2 invasive cancer treated with BCS were included. Rates of positive margins and residual disease at re‐excision were evaluated. 189 patients underwent BCS; 83 had suture marking, 103 had intraoperative inking and 3 had un‐oriented specimens. The incidence of positive margins was 29% (24 patients) in the suture marked group and 20% (21 patients) in the intraoperative inked group ( P  = .18). Among the 45 patients with positive margins, 60% of tumors were stage T1, 76% were node negative, 36% were palpable with median tumor size of 1.5 cm. Residual disease was identified on re‐excision in 21% of the suture marked specimens and 57% of intraoperative inked specimens ( P  = .028). The incidence of residual cancer at re‐excision for positive margins was higher for intraoperatively inked versus suture marked specimens. This finding suggests that intraoperative inking is more effective at guiding re‐excision of positive margins.